2012
DOI: 10.1534/genetics.112.143081
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Molecular Networks That Either Affect or Respond to Plasma Cortisol Concentration in Target Tissues of Liver and Muscle

Abstract: Cortisol is a steroid hormone with important roles in regulating immune and metabolic functions and organismal responses to external stimuli are mediated by the glucocorticoid system. Dysregulation of the afferent and efferent axis of glucocorticoid signaling have adverse effects on growth, health status, and well-being. Glucocorticoid secretion and signaling show large interindividual variation that has a considerable genetic component; however, little is known about the underlying genetic variants. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 65 publications
1
28
0
1
Order By: Relevance
“…In the present study, serum and salivary cortisol were unaffected, but this latter presented high individual variation, suggesting that the perception of stress was variable between animals [23, 24]. …”
Section: Discussionmentioning
confidence: 83%
“…In the present study, serum and salivary cortisol were unaffected, but this latter presented high individual variation, suggesting that the perception of stress was variable between animals [23, 24]. …”
Section: Discussionmentioning
confidence: 83%
“…The cDNA sequence analysis of parental strains revealed a Met276Ile mutation in WKY rat identical to that found in the Biobreeding rat strain that exhibits decreased CBG binding affinity for corticosterone (14). More recently, a series of studies conducted in different pig lines confirmed the genetic linkage or genetic association between SerpinA6/CBG locus and basal cortisol levels in pig (1518). Finally, in humans, a very significant association between the SERPINA6/SERPINA1 locus and morning plasma cortisol concentrations was reported in a genome-wide association meta-analysis using ~2.5 M SNPs in 12,597 Caucasian subjects, replicated in 2,795 participants (19).…”
Section: Genetic Studies Highlighting the Central Role Of Cbg In Gc Vmentioning
confidence: 86%
“…Physiological effects of circulating glucocorticoids are mediated mainly by the glucocorticoid receptor (GR), encoded by NR3C1 (nuclear receptor subfamily 3, group C, member 1). This ubiquitously expressed receptor forms a specific binding complex with glucocorticoids and after activation acts as a transcription factor regulating expression of 5-20% of genes (Galon et al, 2002;Ponsuksili et al, 2012). Main physiological effects of glucocorticoids mediated by genomic actions of GR are regulation of the activity of the immune system and of energy metabolism in liver and skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating levels of glucocorticoids and target tissue response to them show large inter-individual variation and are directly and indirectly related to behavioral, physiological, and metabolic disturbances in mammals (de Groot et al, 2001;Murani et al, 2010Murani et al, , 2011Ponsuksili et al, 2012). The pig becomes increasingly important as an animal model for human diseases because of high physiological and genomic similarities between pigs and humans (Boullion et al, 2003;Kuzmuk and Schook, 2011).…”
Section: Introductionmentioning
confidence: 99%